2009
DOI: 10.4049/jimmunol.0803520
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tumor Metastasis in Response to Blockade of the Chemokine Receptor CXCR6 Is Overcome by NKT Cell Activation

Abstract: Invariant NKT (iNKT) cells can induce potent antitumor responses in vivo. However, the mechanisms that regulate the effects of iNKT cells are unclear. The chemokine receptor CXCR6, and its ligand CXCL16, have been shown to play critical roles in iNKT cell homeostasis and activation. Thus we investigated the role of CXCR6 in protection against experimental metastasis of B16-F10 melanoma (B16) and Lewis lung carcinoma (LLC) cells to the liver and lungs. Wild-type and CXCR6−/− mice exhibited no differences in tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 58 publications
4
63
0
Order By: Relevance
“…7,15,16,21,30,31 Although clinical trials examining NKT cell activation therapies in patients with advanced/recurrent disease have reported few cases of objective tumor regression, tumors tended to remain stable without the appearance of new metastatic foci. 15,[17][18][19][20]35 This suggests that NKT cell activation therapy might be more effective at targeting metastatic disease than primary tumors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7,15,16,21,30,31 Although clinical trials examining NKT cell activation therapies in patients with advanced/recurrent disease have reported few cases of objective tumor regression, tumors tended to remain stable without the appearance of new metastatic foci. 15,[17][18][19][20]35 This suggests that NKT cell activation therapy might be more effective at targeting metastatic disease than primary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…While Th1 skewing is important for tumor control in mouse models, 31,33,34 and elevated IFNg production is associated with prolonged survival in clinical trials, 20,35 we previously found that OCH treatment effectively controlled metastasis of B16 melanoma and Lewis lung carcinoma cells to the liver in C57BL/6 mice. 7 It is likely that the ratio of Th1:Th2 cytokines ultimately impacts tumor control, and differences in immune skewing between BALB/c and C57BL/6 mice could influence the effect of OCH. We focused on a-GalCer in this study because it has been used extensively in human clinical trials where it has been shown to be safe and well tolerated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NKT cells directly eradicate target cells through cell death inducing ligands FasL and TNF-related apoptotic induced ligand (TRAIL) [69] . The recruitment of leukocytes into tissues is dependent on a series of adhesive and activation steps mediated by adhesion molecules and interaction of chemokine and chemokine receptors, which restrict their tissue and microenvironmental distribution [70][71][72] . In this regard, NKT cells resemble effector T cells because CD4 + , CD8 + , and DN subsets uniformly express non-lymphoidtissue-homing chemokine receptors, such as CCR2, CCR5, and CXCR3 [70] .…”
Section: Nkt Cells In Tumor Immunitymentioning
confidence: 99%